From Spermiogram to Bio-Functional Sperm Parameters: When and Why Request Them? - Condorelli, Rosita A. (J Clin Med, 2020)
The aim of this experimental study was to evaluate whether infertile patients may benefit from the evaluation of bio-functional sperm parameters in addition to the conventional semen analysis. To accomplish this, we evaluated the correlation between conventional and bio-functional sperm parameters based on their percentile distribution in search of a potential threshold of these latter that associates with conventional sperm parameter abnormalities. The study was conducted on 577 unselected patients with infertility lasting at least 12 months. We identified cut-off values according to the median of the population for mitochondrial membrane potential (MMP), number of alive spermatozoa, and chromatin abnormality. High MMP (HMMP) (≥46.25%) was associated with sperm concentration, sperm count, progressive motility, and normal form. Low MMP (LMMP) (≥36.5%) was found to be associated with semen volume, sperm concentration, total sperm count, progressive motility, total motility, and normal form. The number of alive spermatozoa (≥71.7%) was associated with sperm concentration and progressive motility whereas abnormal chromatin compactness (≥21.10%) was associated with sperm concentration, total sperm count, and progressive motility. The data would suggest that, for every increase in the percentile category of sperm concentration, the risk of finding an HMMP≤46.25 is reduced by 0.4 and by 0.66 for a total sperm count. This risk is also reduced by 0.60 for every increase in the percentile category of sperm progressive motility and by 0.71 for total sperm motility. Each increment of percentile category of the following sperm parameter was followed by a decrease in the risk of finding an LMMP≤36.5: sperm concentration 1.66, total sperm count 1.28, sperm progressive motility 1.27, total sperm motility 1.76, and normal form 1.73. Lastly, the data showed that, for every increase in the percentile category of total sperm count, the risk of finding an abnormal chromatin compactness ≤21.10 is reduced by 1.25 (1.04–1.51, p < 0.05) and an increase of total sperm motility is associated with a reduced risk by 1.44 (1.12–1.85, p < 0.05). Results suggest a correlation between bio-functional and conventional sperm parameters that impact the sperm fertilizing potential. Therefore, the evaluation of bio-functional sperm parameters by flow cytometry may be useful to explain some cases of idiopathic male infertility.